Listen to the voice of the Earth learn about earthquakes to save lives - Oki, Satoko 1978- (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan), 2015)
A seismologist explains what causes earthquakes and how we can live with them to protect our lives.